Processing of Deep-sea Nodules by Silicothermic Reduction - Borkovcová, Klára; Novák, Pavel; Chmelíková, Eliška (Manufacturing Technology Journal, 2023)
Deep-sea nodules are ores formed on the sea floor at depths of 3000 to 6000 m as a result of sedimen-tation. They range in size from 1 cm to 15 cm and contain mainly manganese and iron and other ele-ments that are collected from the nodules by complex pyrometallurgical and hydrometallurgical pro-cesses. These other elements of interest are bound in the nodules mainly in the form of manganese and iron oxides. In order to achieve a high yield of metals bound in nodules in the form of oxides, it is necessary to disintegrate this arrangement in the lattice. This can be achieved by exposing the deep-sea nodules to a reducing condition. This paper deals with the one-step recovery of metals of interest from nodules using silicothermic reduction with 10% excess silicon over stoichiometry. The phase composition, microstructure and mechanical properties of the obtained reduced material were determined.
Keywords: Deep-sea nodules; Silicothermic reduction; Microstructure